2009
DOI: 10.1111/j.1463-1326.2008.01023.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of vildagliptin and pioglitazone in patients with type 2 diabetes inadequately controlled with metformin

Abstract: When added to metformin, vildagliptin demonstrates favourable safety and tolerability over 1 year. Vildagliptin provided additional HbA(1c) lowering to that achieved with metformin alone and comparable to that achieved with pioglitazone, with only pioglitazone causing weight gain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(71 citation statements)
references
References 18 publications
3
67
0
1
Order By: Relevance
“…The characteristics and outcomes of the trials are reported in Tables 1 and 2. 14,15,[17][18][19][20][21][22][23][24][25][26][27] In the 17 available trials for lipid parameters, Kendall's tau value suggested major publication bias. Not RCT n=14…”
Section: Resultsmentioning
confidence: 97%
“…The characteristics and outcomes of the trials are reported in Tables 1 and 2. 14,15,[17][18][19][20][21][22][23][24][25][26][27] In the 17 available trials for lipid parameters, Kendall's tau value suggested major publication bias. Not RCT n=14…”
Section: Resultsmentioning
confidence: 97%
“…For example, sitagliptin was well tolerated with no increased risk of hypoglycemia as an add-on to pioglitazone versus pioglitazone monotherapy (incidence rate: 1.1% vs. 0%), 35 as add-on to metformin versus metformin monotherapy (1.3% vs 2.1%), 36 as add-on to metformin versus sitagliptin monotherapy (no hypoglycemia events in either group), 37 and as add-on to metformin versus glipizide plus metformin (4.9% vs. 32.0%). 38 Similarly, there was a low incidence of hypoglycemia with vildagliptin plus metformin compared with pioglitazone plus metformin (0.3% vs. 0%) 39 and compared with metformin monotherapy (0% vs 0.7%). 40 The current analysis supports these findings, demonstrating that the DPP-4 inhibitors are well tolerated with a low risk of hypoglycemia when used as monotherapy or add-on to OAD therapy.…”
Section: ■■ Discussionmentioning
confidence: 99%
“…However, in the present review, only head-to-head trials vs active comparators are presented in brief. Gliptins have also been compared with SUs (glimepiride, glipizide, gliclazide) [27][28][29][30][31][32][33][34], TZDs (pioglitazone 30 mg, rosiglitazone 8 mg) [35][36][37][38][39] and GLP-1 receptor agonists (exenatide, liraglutide) [36,40,41]. However, only one head-to-head study compared two different DPP-4 inhibitors in the same trial: saxagliptin 5 mg with sitaglitptin 100 mg as add-ons to basal metformin therapy [42].…”
Section: Gliptins Combined With Metforminmentioning
confidence: 99%